Insights gained from two decades of intensive monitoring: hydrology and nitrate export in a tile-drained agricultural catchment - Bauwe, Andreas; Lennartz, Bernd (Frontiers in Water, 2024)
Nitrate (NO3-) export from agricultural land poses an ongoing threat to both inland and coastal waters. Experimental studies investigating the hydrology-NO3--export mechanisms require long-term data to identify reliable causal relationships. In this study, utilizing a 23-year continuous dataset with a high temporal resolution (daily to twice a week), we aim to identify potential drivers for NO3- losses and assess the impact of nitrogen (N) soil surface budgets on NO3- export. A drainage plot (4.2 ha) and a ditch catchment (179 ha) were fully equipped to register hydrological parameters, including water sample collection. Mean annual NO3--N concentrations (loads) for the drainage plot and the ditch catchment were 9.4 mg l⁻¹ (20.6 kg ha⁻¹) and 6.0 mg l⁻¹ (20.9 kg ha⁻¹), respectively. Annual discharge was closely positively correlated with annual NO3- losses, highlighting the significant influence of prevailing weather and, consequently, hydrologic conditions on NO3- export rates. The majority of the annual NO3--load was exported during winter (56% at the drainage plot, 51% at the ditch catchment), while the rest was exported during spring (28%, 29%), summer (9%, 9%) and fall (7%, 11%). We could not find any direct relationships between N soil surface budgets and NO3- losses. Putting all results together, it can be concluded that agricultural activities for many decades resulted in high soil N stocks, which determined the general high NO3--N concentration levels. Nevertheless, temporal NO3- export dynamics during the last two decades were clearly driven by hydro-meteorological conditions, nearly independently of land management and N soil surface budgets on the fields.